An Entropy-Based Model for Basal Ganglia Dysfunctions in Movement Disorders. (16th May 2013) - Darbin, Olivier; Dees, Daniel; Martino, Anthony; Adams, Elizabeth; Naritoku, Dean
Abstract : During this last decade, nonlinear analyses have been used to characterize the irregularity that exists in the neuronal data stream of the basal ganglia. In comparison to linear parameters for disparity (i.e., rate, standard deviation, and oscillatory activities), nonlinear analyses focus on complex patterns that are composed of groups of interspike intervals with matching lengths but not necessarily contiguous in the data stream. In light of recent animal and clinical studies, we present a review and commentary on the basal ganglia neuronal entropy in the context of movement disorders.